STUDENTS’ PERCEPTION IN ENGLISH TEACHING AND LEARNING CONCERNING NATIVE-SPEAKERISM - Ofel Rondonuwu; Nihta Liando; Sanerita Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
Native-speakerism issues are found in English teaching and learning around the world. This study aims to clarify how students perceive something like the characteristics of an ideal English teacher, and how students perceive learning English. This study was conducted at the Faculty of English Education, Faculty of Languages and Arts, Universitas Negeri Manado. A 17-item questionnaire taken from a previous related study was used and distributed to 32 students. The results of this study showed that most students do not recognize “native speakers” as a source of credibility and that the role model for imitating accents should be “native speakers”. Both “native speakers” and “non-native speakers” are recognized as equally good in grammar lessons.